Clear history [videorecording (DVD)] - David, Larry; David, Larry; Mottola, Greg; Hader, Bill, 1978-; Hall, Philip Baker, 1931-; Hamm, Jon, 1971-; Hudson, Kate, 1979-; Keaton, Michael, 1951-; McBride, Danny, 1976-; Mendes, Eva, 1974-; Ryan, Amy; Smoove, J. B., 1964- (Home Box Office ; Distributed by Warner Home Video, 2013)
Ten years ago, Nathan was the successful head of marketing for a start-up electric car company. A disagreement with his boss led Nathan to walk away and sell his stock. Soon after, the company became wildly successful, humiliating Nathan who fled into exile. A decade later, Nathan lives a simple life on Martha's Vineyard and goes by the alias 'Rolly DeVore'. But when his old boss shows up, Nathan/Rolly vows to drive him off the island before his true identity is uncovered.